(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2024)
Background: KRT (High Risk Pregnancy) has a risk of complications during childbirth with the impact of death, morbidity, disability, dissatisfaction and discomfort. Undetected KRT and late referral are the main causes of maternal and infant deaths. The number of high-risk pregnant women at the Muara Community Health Center must be above the target set by the district, namely below 20%. One of the causes of maternal death is late detection of KRT, therefore researchers are interested in knowing the factors that cause high risk pregnant women. Objective: To find out the factors associated with the incidence of high risk pregnant women in Muara Community Health Centers. Method: This type of research uses quantitative research methods with a cross sectional approach. The sampling technique is total sampling. The population and sample of this study were high-risk pregnant women. The analysis used is the chi-square test. Results: The research results show that the job variable has an exact sig value. is >0.05, namely 0.647, then the alternative hypothesis (H0) is rejected, which means there is no relationship between work and the incidence of high risk pregnant women. Environmental and genetic variables have exact sig values. is <0.05, namely 0.028 in the environment and 0.045 in genetics, then the alternative hypothesis (Ha) is accepted, there is a significant relationship between variables (environment, genetics) and the incidence of high risk pregnancy. Conclusion: Research shows that there is a significant relationship between environment and genetics and the incidence of high-risk pregnant women. There is no significant relationship between work and the incidence of high-risk pregnant women, which means that the work reported by high-risk pregnant women at the Muara Should Community Health Center is not too dangerous for pregnancy.